Synthesis and crystallographic analysis of meso-2,3-difluoro-1,4-butanediol and meso-1,4-dibenzyloxy-2,3-difluorobutane - Linclau, Bruno; Leung, Leo; Nonnenmacher, Jean; Tizzard, Graham (Beilstein Journal of Organic Chemistry, 2010)
A large-scale synthesis of meso-2,3-difluoro-1,4-butanediol in 5 steps from (Z)-but-2-enediol is described. Crystallographic analysis of the diol and the corresponding benzyl ether reveals an anti conformation of the vicinal difluoride moiety. Monosilylation of the diol is high-yielding but all attempts to achieve chain extension through addition of alkyl Grignard and acetylide nucleophiles failed.
Keywords: building block; epoxide opening; gauche effect; organofluorine; vicinal difluoride